2016
DOI: 10.1021/acs.jpcc.6b06853
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Charge Transfer Dynamics in Colloidal CsPbBr3 Perovskite Quantum Dots Sensitized Molecular Adsorbate

Abstract: Ultrafast charge-transfer (CT) dynamics has been verified in CsPbBr 3 (CPB) quantum dot (QD)−4,5-dibromofluorescein (DBF) composite materials, which form a strong CT complex in the ground state and can absorb more photons in the red region of the solar spectrum. Cyclic voltammetry and steady state luminescence studies suggest that the conduction (CB) and valence bands (VB) of CPB lie, respectively, below the LUMO and the HOMO of the DBF molecule. Steady state and time-resolved luminescence measurements with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 44 publications
(73 reference statements)
3
54
1
2
Order By: Relevance
“…Several studies have already shown that perovskite NCs possess great potential for solution‐processable photovoltaic devices under ambient atmosphere due to their high environmental and thermodynamic stabilities . Other studies demonstrate the charge transfer dynamics for perovskite NCs in heterojunctions showing great potential for charge extraction in further applications . Most reported perovskite photovoltaic devices are generally fabricated in a layer‐by‐layer configuration in which the exciton dissociation occurs at the interface of the perovskite NC layer and the respective electron or hole‐transport layer.…”
Section: Responsivity (R) and Detectivity (D*) Of Photodetectors Undementioning
confidence: 99%
“…Several studies have already shown that perovskite NCs possess great potential for solution‐processable photovoltaic devices under ambient atmosphere due to their high environmental and thermodynamic stabilities . Other studies demonstrate the charge transfer dynamics for perovskite NCs in heterojunctions showing great potential for charge extraction in further applications . Most reported perovskite photovoltaic devices are generally fabricated in a layer‐by‐layer configuration in which the exciton dissociation occurs at the interface of the perovskite NC layer and the respective electron or hole‐transport layer.…”
Section: Responsivity (R) and Detectivity (D*) Of Photodetectors Undementioning
confidence: 99%
“…Com isso, PQs de perovsquitas à base de chumbo tri-halogeneto de césio (CsPbX 3 ), completamente inorgânico, têm sido estudados atualmente como uma alternativa para aplicação em células solares, 100 uma vez que já foi reportada a montagem de um dispositivo fotovoltaico sensibilizado com PQs de perovsquitas híbridos pela primeira vez em 2011, obtendo-se eficiência de conversão de 6,5%. 101 Em 2016, PQs coloidais de perovsquitas inorgânicos foram aplicados como sensibilizadores, por Kulbak e colaboradores, 102 obtendo 6,6% de eficiência de conversão de energia, apresentando maior estabilidade em relação às perovsquitas à base de metilamônio.…”
Section: Células Solares Sensibilizadas Por Pontos Quânticosunclassified
“…Notably, the highest charge carrier lifetime was observed for stoichiometrically balanced samples, while impurities in the other two samples led to creation of nonradiative recombination sites . In another report, issues pertaining to narrow absorption in the solar spectrum and low charge dynamics in CsMX 3 perovskites are resolved by cosynthetization of a dibromofluorecein‐CsPbBr 3 quantum dot complex …”
Section: Applications Of Inorganic and Layered Perovskite Materialsmentioning
confidence: 98%